Present status of Krishna Valley cattle: An endangered breed of cattle - Gokhale, S B; Bhagat, R L (The Indian Journal of Animal Sciences, 2012)
Study of 500 farmer families in the breed tract indicated that very few number Krishna Valley animals exist in the tract and are maintained by few farmer families. Comparatively poor socio-economic status of community accompanied by lower conditions, literacy and preference for maintaining this breed type indicate the capacity of these animals to perform in hard. The variation observed during phenotypic type scoring indicated possible mixing of this breed with other cattle breeds. To save the breed from extinction, breed specific programmes for phenotypic purification of the mixed population need be taken up by genetic selection approach for conservation and improvement of this breed.